2021
DOI: 10.1017/s1049023x21000194
|View full text |Cite
|
Sign up to set email alerts
|

Do Clothing Labels Play a Role for Weight Estimation in Pediatric Emergencies? A Prospective, Cross-Sectional Study

Abstract: Introduction: The aim of this study was to investigate the usability of the age value listed on the labels on children’s clothes in the age-based weight estimation method recommended by the Pediatric Advanced Life Support (PALS) guidelines. Material-Method: This prospective, cross-sectional study was organized in Antalya Training and Research Hospital Emergency Department. Children aged between 1-12 years were included in the study. The weight measurements of the children were obtained b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
0
0
Order By: Relevance
“…14 In the absence of a known age, clothing label ages (6-month, 12-month, etc) may be used as an acceptable substitute. 15 However, in an emergency setting, the majority of these schemes have been found to be less practical. A preliminary study 16 has shown that these more objective weight estimate measurements are more accurate than a clinician's estimate for pediatric patients.…”
Section: Resultsmentioning
confidence: 99%
“…14 In the absence of a known age, clothing label ages (6-month, 12-month, etc) may be used as an acceptable substitute. 15 However, in an emergency setting, the majority of these schemes have been found to be less practical. A preliminary study 16 has shown that these more objective weight estimate measurements are more accurate than a clinician's estimate for pediatric patients.…”
Section: Resultsmentioning
confidence: 99%